Pembagian Hak Waris Antara Pewaris Berbeda Agama Dengan Ahli Waris - Luchia Saldi, Sindi; Fitri, Devianty (Magister Kenotariatan, Universitas Jambi, 2023)
The purpose of this research is to analyze the status of inheritance rights of children of different religions with their heirs according to Islamic law and try to resolve the distribution of inheritance rights to children of different religions according to Islamic law. The problem of inheritance among different religions has now become a modern problem because neither the Koran nor the hadiths explain the distribution of assets between heirs of different religions. This research approach uses normative legal research. The results of the study show that the inheritance rights for children of different religions are regulated according to Islamic law in the hadith and the Compilation of Islamic Law, where non-Muslim children are not entitled to inheritance. However, in practice, in court decisions, judges give inheritance shares to children of different religions on the basis of a binding will. This violates Islamic provisions and the Islamic Law Compilation. However, the decision regarding inheritance is the implementation of justice, interests and legal certainty in family life. According to Islamic law, the inheritance rights of children of different religions are distributed through grants and wills. This is in accordance with the provisions of the Al-Qur'an, Hadith and Compilation of Islamic Law which are permissible in terms of scholarships for both Muslims and non-Muslims. The judge uses a will in a court decision regarding the division of inheritance.